PRMT5 promotes epithelial‐mesenchymal transition via EGFR‐β‐catenin axis in pancreatic cancer cells. Issue 2 (18th December 2019) - Ge, Lu; Wang, Huizhi; Xu, Xiao; Zhou, Zhengrong; He, Junbo; Peng, Wanxin; Du, Fengyi; Zhang, Youli; Gong, Aihua; Xu, Min
Abstract: Protein arginine methyltransferase 5 (PRMT5) has been implicated in the development and progression of human cancers. However, few studies reveal its role in epithelial‐mesenchymal transition (EMT) of pancreatic cancer cells. In this study, we find that PRMT5 is up‐regulated in pancreatic cancer, and promotes proliferation, migration and invasion in pancreatic cancer cells, and promotes tumorigenesis. Silencing PRMT5 induces epithelial marker E‐cadherin expression and down‐regulates expression of mesenchymal markers including Vimentin, collagen I and β‐catenin in PaTu8988 and SW1990 cells, whereas ectopic PRMT5 re‐expression partially reverses these changes, indicating that PRMT5 promotes EMT in pancreatic cancer. More importantly, we find that PRMT5 knockdown decreases the phosphorylation level of EGFR at Y1068 and Y1172 and its downstream p‐AKT and p‐GSK3β, and then results in down‐regulation of β‐catenin. Expectedly, ectopic PRMT5 re‐expression also reverses the above changes. It is suggested that PRMT5 promotes EMT probably via EGFR/AKT/β‐catenin pathway. Taken together, our study demonstrates that PRMT5 plays oncogenic roles in the growth of pancreatic cancer cell and provides a potential candidate for pancreatic cancer treatment.